Hsp90 Inhibitors Prevent HSV-1 Replication by Directly Targeting UL42-Hsp90 Complex - Qin, Shurong; Hu, Xiao; Lin, Shimin; Xiao, Ji; Wang, Zhaoyang; Jia, Jiaoyan; Song, Xiaowei; Liu, Kaisheng; Ren, Zhe; Wang, Yifei (Frontiers in Microbiology, 2022)
Herpes simplex virus type I (HSV-1) is a member of the Alphaherpesvirinae family, which could initiate labial herpes caused by the reactivation of HSV-1 primary infection, and genital herpes caused by secondary infection even causes herpes encephalitis. The study presented here demonstrates that new Hsp90 inhibitors AT-533 and 17-AAG directly prevent the replication of HSV-1 without affecting RNA transcription. Other mechanisms revealed that Hsp90 inhibitors (AT-533 and 17-AAG) directly targeted the HSV-1 UL42-Hsp90 complex, and Hsp90 interacted with HSV-1 UL42 in silicon and experiment. Interestingly, Hsp90 inhibitors also reduced ACV-resistant clinical HSV-1 strains (153 and blue strain) virus titers and DNA copy numbers, revealing that HSV-1 UL42 would be a new target against ACV-resistant HSV-1 strains. Altogether, this present study indicates that Hsp90 inhibitors prevent HSV-1 replication by regulating the interaction between Hsp90 and HSV-1 UL42 and suggests a promising target for anti-HSV-1 therapies in the replication.